Seleção de aços e de lubrificação para rolamentos usados em sistema de exaustão industrial - Rocha, Rodolfo Martins (Universidade Federal de São Carlos, 2024)
Industrial exhaust systems are of extreme importance for the proper functioning of an industry. Responsible for removing polluting gases from an internal environment to the external environment, industrial exhaust fans have the function of transporting air with the objective of controlling temperature, humidity, moving particles, and other environmental elements to the outside through air displacement. For this to be possible, the fan must be coupled to a system composed of motors, shafts, and bearings. For this system to operate, the components must be capable of functioning in the given environment, as many of these environments are considered corrosive and abrasive, leading to surface wear of the components and, eventually, system failure. One component that must be considered is the bearings, as they are responsible for moving the fan shafts and must withstand high loads, high speeds, and vibrations. Lack of maintenance and misalignment of the fans are some of the causes of surface defects in bearings and, consequently, the bending of the device. Since bearings are made of an articulated structure, they require materials that can withstand, in addition to loads, high speeds and large numbers of rotations, requiring materials with high fatigue resistance and hardness. The most commonly used materials for manufacturing these devices are steels. Among the different types of steels in the materials field, the most used for bearings are high-carbon steels and tool steels. Due to the presence of carbon and other alloying elements, these materials exhibit good hardness and fatigue resistance. In addition to steels, another important material for the proper functioning of bearings is lubricants. Responsible for reducing friction between the rolling surfaces of the bearing, lubricants function by replacing direct friction (metal on metal) with fluid friction (metal with a thin layer of lubricant), thereby increasing the bearing's service life and preventing structural damage. Thus, this study seeks to select alternative steels and lubricants applicable to bearings through the GRANTA Edupack software (for steels only) and classify the best option selected using the TOPSIS method. For the steels, the properties important for application in bearings were considered in two scenarios: reference scenario and priority scenario. Among the options presented, the cold-work AISI D3 steel (C: 2.00% / Mn: 0.30% / Si: 0.25% / Cr: 11.50%) received the best classification, and for the lubricant, LGMT 2 lubricant, whose thickener is lithium soap based on mineral oil, ranked highest.
Selection of steels and lubrication for bearings used in industrial exhaust systems
Keywords: Ventilador; Rolamento; Aço; Lubrificante; Desgaste; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA